Lithium iron phosphate material and preparation method thereof, positive pole piece and secondary battery

By using lithium iron phosphate material with bimodal distributed particle size, combined with the combination of large and small particles, the tap density and specific surface area of ​​the material are improved, and the specific capacity and rate performance of lithium iron phosphate material are solved, and better electrochemical performance is achieved.

CN119725521AActive Publication Date: 2025-03-28GUANGDONG BRUNP RECYCLING TECH CO LTD

Patent Information

Application Number
CN202510228499.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-03-28
Estimated Expiration
2045-02-28

AI Technical Summary

Technical Problem

The tap density and actual specific capacity of lithium iron phosphate materials are relatively low, and the lithium ion transmission rate is slow, which affects the rate performance.

Method used

The lithium iron phosphate material with a bimodal distribution particle size distribution curve is used to improve the tap density and specific surface area of ​​the material through the combination of large particles and small particles, thereby improving the specific capacity and rate performance. The specific method includes coating the large-sized iron phosphate seeds with polydopamine, mixing them with the small-sized iron phosphate seeds after vacuum dehydration, performing precipitation reaction and baking, and producing lithium iron phosphate material with excellent properties.

Benefits of technology

The high tap density and specific surface area of ​​lithium iron phosphate materials are achieved, and its specific capacity and rate performance are improved, solving the problem of insufficient material performance improvement in traditional grading methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725521A_ABST
    Figure CN119725521A_ABST
Patent Text Reader

Abstract

The invention provides a lithium iron phosphate material and a preparation method thereof, a positive pole piece and a secondary battery, and relates to the field of positive pole materials. The lithium iron phosphate material meets the condition that sigma b / sigma f is larger than or equal to 1.10 and smaller than or equal to 5.00, sigma b is the sample standard deviation of the circularity C of large-particle lithium iron phosphate, sigma f is the sample standard deviation of the circularity C of small-particle lithium iron phosphate, and the large-particle lithium iron phosphate and the small-particle lithium iron phosphate with different morphologies are matched with each other through the difference of the sample standard deviation of the circularity of the large-particle lithium iron phosphate and the sample standard deviation of the circularity of the small-particle lithium iron phosphate. Therefore, the lithium iron phosphate material has good tap density and specific surface area. According to the preparation method of the lithium iron phosphate material, the large-particle-size iron phosphate seed crystal partially coated with polydopamine is subjected to vacuum dehydration to obtain the modified iron phosphate seed crystal with the dehydrated surface layer, the morphology of the large-particle iron phosphate prepared by precipitation reaction is influenced, and the iron phosphate material is obtained by utilizing the large and small seed crystals through a coprecipitation method. And finally, the lithium iron phosphate material with good tap density and specific surface area is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of positive electrode materials, and in particular to a lithium iron phosphate material and a preparation method thereof, a positive electrode sheet and a secondary battery. Background Art

[0002] Lithium iron phosphate (LiFePO4) with olivine structure is a type of positive electrode material for secondary batteries. It has the characteristics of wide raw material source, low price, good thermal stability, environmental friendliness and stable discharge platform, making it one of the most promising positive electrode materials.

[0003] However, the low tap density and low actual specific capacity of lithium iron phosphate materials limit their development. There is a close relationship between the tap density of lithium iron phosphate materials and the particle size of the particles. If the powder composed of particles has an ideal particle size distribution so that small particles can fill the gaps between large particles as much as possible, its tap density can be further improved, which is beneficial to improving the volume specific capacity of secondary batteries.

[0004] In this field, large and small particle grading is usually used to improve the tap density of lithium iron phosphate materials. However, since lithium ions in lithium iron phosphate materials mainly diffuse along one-dimensional direction, the transmission speed of lithium ions inside the material is slow. The grading method still cannot effectively alleviate the problem of reduced rate performance caused by slow ion transmission rate in lithium iron phosphate materials.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The purpose of the present invention includes providing a lithium iron phosphate material and a preparation method thereof, a positive electrode plate and a secondary battery. The particle size distribution curve of the lithium iron phosphate material is a bimodal distribution, and the standard deviation of the circularity of large-particle lithium iron phosphate is greater than the standard deviation of the circularity of small-particle lithium iron phosphate. Large-particle lithium iron phosphate and small-particle lithium iron phosphate with different morphologies cooperate with each other, so that the lithium iron phosphate material has good tap density and specific surface area, and thus has better specific capacity and rate performance.

[0007] In order to achieve the above-mentioned object, the present invention provides a lithium iron phosphate material in the first aspect. The particle size distribution curve of the lithium iron phosphate material is a bimodal distribution. The particle size distribution curve includes a first peak and a second peak in the positive direction of the horizontal axis. The particle sizes corresponding to the first peak and the second peak are D f and D b , in μm; the corresponding volume percentages are V f and V b ; Lithium iron phosphate material meets 1.10≤σ b / σ f ≤5.00, where σ bis the sample standard deviation of the circularity C of large-particle lithium iron phosphate, σ f is the sample standard deviation of the circularity C of small-particle lithium iron phosphate, circularity C=(4×π×A) / P 2 , A is the projected area of ​​the lithium iron phosphate particle, and P is the perimeter of the projected area; Large particle lithium iron phosphate has a projected area greater than or equal to S max =1 / 4×π×D b 2 The projected area of ​​lithium iron phosphate particles is less than or equal to S min =1 / 4×π×D f 2 of lithium iron phosphate particles.

[0008] In some embodiments, the lithium iron phosphate material satisfies at least one of the following features 1 and 2: Feature 1: σ b Satisfy 0.05≤σ b ≤0.15; Feature 2: σ f Satisfy 0.02≤σ f ≤0.09.

[0009] In some embodiments, the lithium iron phosphate material satisfies at least one of the following features ad: Feature a: 0.3μm≤D f ≤1.0μm and 1.2μm≤D b ≤10μm; Feature b: 3%≤V f ≤10% and 3%≤V b ≤10%; Characteristic c: 0.2 ≤ V b / V f ≤2.5; Characteristic d: 2.5 ≤ D b / D f ≤12.

[0010] In some embodiments, the lithium iron phosphate material satisfies: ; Wherein, span satisfies 1.5≤span≤5, span=(Dv90-Dv10) / Dv50, Dv90, Dv50 and Dv10 are the particle sizes corresponding to the cumulative volume percentages of lithium iron phosphate materials reaching 90%, 50% and 10%, respectively, and the unit is μm.

[0011] In a second aspect, the present invention provides a method for preparing the lithium iron phosphate material according to the first aspect, comprising: The large-size iron phosphate seed crystals are coated with polydopamine to obtain large-size iron phosphate seed crystals partially coated with polydopamine; Dehydrating the large-size iron phosphate seed crystals partially coated with polydopamine under vacuum to obtain modified iron phosphate seed crystals; The modified ferric phosphate seed crystals and the small-size ferric phosphate seed crystals are mixed, and an iron salt and a phosphorus source are added to carry out a precipitation reaction in water to obtain an ferric phosphate material; The iron phosphate material, the lithium source and the carbon source are mixed and then calcined to obtain the lithium iron phosphate material.

[0012] In some embodiments, the preparation method of large-particle iron phosphate seeds partially coated with polydopamine includes: mixing and dispersing large-particle iron phosphate seeds and a surfactant in a Tris-HCl buffer solution containing dopamine hydrochloride, stirring the reaction, filtering, washing, and drying to obtain large-particle iron phosphate seeds partially coated with polydopamine.

[0013] In some embodiments, the method for preparing large-size iron phosphate seeds partially coated with polydopamine includes at least one of the following features 1 to 6: Feature 1: The surfactant is an anionic surfactant, and the concentration of the surfactant in the Tris-HCl buffer solution is 0.1-3 g / L; Feature 2: The mass ratio of large-size iron phosphate seeds to surfactant is 50:1~5; Feature 3: The particle size of large-size iron phosphate seeds is 400-1500nm; Feature 4: The pH of Tris-HCl buffer solution is 8-8.5; Feature 5: The concentration of dopamine hydrochloride in Tris-HCl buffer solution is 0.1-0.3 mg / mL; Feature 6: The stirring rate of the stirring reaction is 500-1000 rpm and the time is 20-30 hours.

[0014] In some embodiments, the method for preparing the lithium iron phosphate material includes at least one of the following features AG: Feature A: The vacuum dehydration temperature is 160-190°C and the time is 1-1.5h; Characteristic B: The particle size of the small-size iron phosphate seed crystals is 200-600 nm; Characteristic C: the volume ratio of the modified iron phosphate seed crystals to the small-size iron phosphate seed crystals is 0.9-1.5:1; Characteristic D: the volume ratio of the total volume of the modified iron phosphate seed crystals and the small-size iron phosphate seed crystals to the volume of water is 1:4-12; Characteristic E: The concentration of iron salt in water is 0.5-1.2 mol / L; Feature F: The molar ratio of the iron element of the iron salt to the phosphorus element of the phosphorus source is 1:1-1.5; Feature G: The stirring rate of the precipitation reaction is 350-750 rpm.

[0015] The present invention provides a positive electrode plate in a third aspect, comprising the lithium iron phosphate material of the first aspect of the present invention or the lithium iron phosphate material obtained by the preparation method provided in the second aspect of the present invention.

[0016] The present invention provides a secondary battery in a fourth aspect, comprising the positive electrode sheet provided in the third aspect.

[0017] The beneficial effects of the present invention include: The lithium iron phosphate material provided by the present invention satisfies 1.10≤σ b / σ f ≤5.00, where σ b is the sample standard deviation of the circularity C of large-particle lithium iron phosphate, σ f is the sample standard deviation of the circularity C of small-particle lithium iron phosphate. Through the difference in the sample standard deviation of the circularity of large and small particles of lithium iron phosphate material, large-particle lithium iron phosphate and small-particle lithium iron phosphate with different morphologies are matched with each other, so that the lithium iron phosphate material has good tap density and specific surface area.

[0018] The preparation method of the lithium iron phosphate material provided by the present invention comprises the following steps: vacuum dehydrating large-particle iron phosphate seeds partially coated with polydopamine to obtain surface-dehydrated modified iron phosphate seeds, thereby affecting the morphology of large-particle iron phosphate obtained by precipitation reaction, and using large and small seeds through a co-precipitation method to obtain an iron phosphate material, and finally obtaining a lithium iron phosphate material with good tap density and specific surface area. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0020] Figure 1 This is a SEM image of the lithium iron phosphate material provided in Example 1 of the present invention; Figure 2 This is a SEM image of the lithium iron phosphate material provided in Comparative Example 2 of the present invention; Figure 3 This is the particle size distribution curve of the lithium iron phosphate material provided in Example 4-5 of the present invention. DETAILED DESCRIPTION

[0021] Below, with appropriate reference to the accompanying drawings, a lithium iron phosphate material and its preparation method, a positive electrode plate and a secondary battery of the present invention are specifically disclosed. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0022] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. In particular, "()", ")", "[" and "]" represent intervals, where "(" or ")" represents an open interval, that is, the endpoint values ​​of the interval are not included; "[" and "]" represent a closed interval, that is, the endpoints within the interval are included. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range.

[0023] Specifically, for example, if a range of 60-120 and 80-110 is listed for a particular parameter, it is understood that the range of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been fully listed in this article, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a certain parameter is expressed as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. If (10, 20) is listed, it is understood as any value between 10 and 20, excluding 10 and 20; (10, 20] is understood as any value between 10 and 20, excluding 10 but including 20.

[0024] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0025] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0026] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0027] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0028] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0029] Lithium iron phosphate materials have an inherent problem of low ion transmission rate. Particle nano-sizing is an effective means to improve the lithium ion transmission rate. However, while particle nano-sizing shortens the transmission path and improves the rate performance, it also leads to low energy density due to low tap density. Therefore, grading is often used in this field to increase the tap density of the material by utilizing the filling effect between large and small particles. However, since large particles have a lower specific surface area and a longer ion diffusion path, the tap density of the material is increased by grading, but the specific surface area of ​​the material is reduced, and the rate performance of the material is not significantly improved.

[0030] In a first aspect, the present invention provides a lithium iron phosphate material. The particle size distribution curve of the lithium iron phosphate material is a bimodal distribution. The particle size distribution curve includes a first peak and a second peak in the positive direction of the horizontal axis. The particle sizes corresponding to the first peak and the second peak are D f and D b , in μm; the corresponding volume percentages are V f and V b ; Lithium iron phosphate material meets 1.10≤σ b / σ f ≤5.00, where σ b is the sample standard deviation of the circularity C of large-particle lithium iron phosphate, σ fis the sample standard deviation of the circularity C of small-particle lithium iron phosphate, circularity C = (4 × π × A) / P 2 , A is the projected area of ​​the lithium iron phosphate particle, and P is the perimeter of the projected area; Large particle lithium iron phosphate has a projected area greater than or equal to S max =1 / 4×π×D b 2 The projected area of ​​lithium iron phosphate particles is less than or equal to S min =1 / 4×π×D f 2 In order to solve the problem that ordinary large and small particle grading can improve the tap density but reduce the specific surface area of ​​lithium iron phosphate positive electrode materials, the present invention provides a lithium iron phosphate material in which the standard deviation of the sphericity of large-particle lithium iron phosphate is greater than the standard deviation of the sphericity of small-particle lithium iron phosphate, and the lithium iron phosphate material has good tap density and specific surface area.

[0031] The circularity C of the projection surface of lithium iron phosphate particles can reflect the sphericity of lithium iron phosphate particles. The closer it is to 1, the better the sphericity of the particles. b and σ f They represent the sample standard deviations of the circularity C of large and small lithium iron phosphate particles, respectively. The larger the sample standard deviation, the higher the dispersion of the circularity C value, which is manifested as a greater difference in the sphericity of the particles; the smaller the sample standard deviation, the higher the circularity. The lower the degree of discreteness, the smaller the difference in sphericity of the particles. The lithium iron phosphate material in the present invention satisfies 1.10≤σ b / σ f ≤5.00 (σb / σf can be 1.10, 1.15, 1.20, 1.25, 1.30, 1.35, 1.40, 1.45, 1.50, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0 or any value between 1.10 and 5.00). The lithium iron phosphate material within this range has good tap density and specific surface area.

[0032] In some embodiments, the σ of the lithium iron phosphate material b Satisfy 0.05≤σ b ≤0.15(σ b It can be 0.05, 0.075, 0.08, 0.085, 0.09, 0.095, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15 or any value between 0.05 and 0.15).

[0033] In some embodiments, the σ of the lithium iron phosphate material f Satisfy 0.02≤σ f ≤0.09(σf It can be 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09 or any value between 0.02 and 0.09).

[0034] Since the surface area of ​​a standard sphere is the smallest under the same volume, the sphericity of lithium iron phosphate material affects its specific surface area and tap density, and ultimately affects its electrochemical performance. Specifically, the higher the sphericity, the smaller the specific surface area of ​​the lithium iron phosphate material, which reduces the contact area between the material and the electrolyte and reduces the lithium ion transmission efficiency; the lower the sphericity, the lower the tap density of the lithium iron phosphate material, which ultimately reduces the volume energy density of the material.

[0035] Generally, the sphericity of lithium iron phosphate particles is relatively uniform, which is beneficial to increase the tap density and reduce the internal resistance. However, the higher the sphericity, the smaller the surface area of ​​the particles, which is not conducive to the improvement of the specific surface area. The present invention provides a lithium iron phosphate material with a bimodal particle size distribution curve, so as to distinguish large lithium iron phosphate particles and small lithium iron phosphate particles in the lithium iron phosphate material, wherein the roundness standard deviation (σ b ) is larger, while the standard deviation of circularity of small-particle lithium iron phosphate (σ f ) is smaller.

[0036] If the uniformity of the sphericity of large-particle lithium iron phosphate is too high or too low, it will not be conducive to improving the overall performance of lithium iron phosphate materials. Specifically, if the sphericity of large-particle lithium iron phosphate is too different, it may be manifested as particles with too low sphericity in the large particles, which will cause the pores formed by the overlap between the particles to be too large, and the material's tap density will be reduced; when the sphericity of large-particle lithium iron phosphate is too small, it may be manifested as all high sphericity, all low sphericity, or other sphericities of the same degree. When all high sphericity leads to a decrease in the total specific surface area of ​​the material, and when all low sphericity leads to a decrease in the tap density of the material, if it is other spherical shapes of the same degree, it will be difficult for the material to have both good tap density and specific surface area. Small-particle lithium iron phosphate fills the gaps between large-particle lithium iron phosphate, plays a role in improving the tap density, and satisfies 0.02≤σ f Small lithium iron phosphate particles with a density of ≤0.09 can well fill the gaps in large lithium iron phosphate particles and increase the tap density of lithium iron phosphate materials.

[0037] In some embodiments, the lithium iron phosphate material satisfies 0.3 μm ≤ D f ≤1.0μm and 1.2μm≤D b ≤10μm (where D f It can be 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm or any value of 0.3-1.0 μm; wherein D bIt can be 1.2μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm or any value between 1.2-10μm).

[0038] In some embodiments, the lithium iron phosphate material satisfies 3%≤V f ≤10% and 3%≤V b ≤10% (V f or V b It can be 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any value between 3% and 10%).

[0039] In some embodiments, the lithium iron phosphate material satisfies 0.2≤V b / V f ≤2.5 (where V b / V f It can be 0.2, 0.5, 1.0, 1.5, 2.0, 2.5 or any value between 0.2-2.5).

[0040] V b / V f Reflects the difference in volume fractions of the two largest particles in the lithium iron phosphate material, that is, reflects the ratio of the number of particles of two sizes. The larger the value, the greater the difference in volume between the two particles, and the smaller the value, the smaller the difference in volume between the two particles. b / V f Too large or too small can not effectively improve the tap density of the positive electrode material. b / V f Too large indicates that the particle size is D f The number of small lithium iron phosphate particles is compared with the particle size D b Too many large lithium iron phosphate particles will reduce the overall specific surface area of ​​the lithium iron phosphate material; b / V f Too small indicates that the particle size is D b Compared with the number of large particles of lithium iron phosphate, the particle size is D f There are too many small particles of lithium iron phosphate. Since the diffusion path formed by the accumulation of small particles of lithium iron phosphate is relatively tortuous and long, it will limit the diffusion of lithium ions and ultimately reduce the rate performance and specific capacity.

[0041] In some embodiments, the lithium iron phosphate material satisfies 2.5≤D b / D f ≤12 (where D b / D fIt can be 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0 or any value between 2.5 and 12).

[0042] D b / D f Reflects the size difference between the two largest particle sizes in the lithium iron phosphate material. The larger the value, the greater the difference between the two particle sizes. The smaller the value, the smaller the difference between the two particle sizes. b / D f If the particle size is too small, the grading effect of the particles cannot be fully utilized, resulting in the failure to effectively improve the tap density of the positive electrode material; D b / D f If the temperature is too high, the small particles of lithium iron phosphate will be "overburned" during the roasting process.

[0043] In some embodiments, the lithium iron phosphate material satisfies: ; Wherein, span = (Dv90-Dv10) / Dv50, satisfying 1.5≤span≤5, and the Dv90, Dv50 and Dv10 are the particle sizes corresponding to the cumulative volume percentages of the lithium iron phosphate material reaching 90%, 50% and 10%, respectively, and the unit is μm.

[0044] Span reflects the overall particle size distribution width of the lithium iron phosphate material. The larger the value, the wider the particle size distribution, and the smaller the value, the narrower the particle size distribution.

[0045] Lithium iron phosphate material meets ( It can be 2, 4, 6, 8, 10, 12, 14, 16, 18, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70 or any value in the range of 2-70). b / D f 、V b / V f , span, and σ b / σ f By coordinating with each other, lithium iron phosphate material has better tap density and specific surface area, and therefore has better specific capacity and rate performance.

[0046] A second aspect of the present invention provides a method for preparing a lithium iron phosphate material, the preparation method comprising: The large-size iron phosphate seed crystals are coated with polydopamine to obtain large-size iron phosphate seed crystals partially coated with polydopamine; vacuum dehydrating the large-size iron phosphate seed crystals partially coated with polydopamine to obtain modified iron phosphate seed crystals; The modified ferric phosphate seed crystals and the small-size ferric phosphate seed crystals are mixed, and an iron salt and a phosphorus source are added to carry out a precipitation reaction in water to obtain an ferric phosphate material; The iron phosphate material, the lithium source and the carbon source are mixed and calcined to obtain the lithium iron phosphate material.

[0047] The present invention uses vacuum dehydration treatment to dehydrate the exposed dihydrate ferric phosphate on the surface of the large-size ferric phosphate seed crystal partially coated with polydopamine into anhydrous ferric phosphate, thereby obtaining a modified ferric phosphate seed crystal having a part of the surface coated with polydopamine and a part of the surface being anhydrous ferric phosphate. Since anhydrous ferric phosphate is easily soluble in an acid solution, during the precipitation reaction, the anhydrous ferric phosphate on the surface of the modified ferric phosphate seed crystal is dissolved by acid to expose dihydrate ferric phosphate, and the dihydrate ferric phosphate can continue to grow ferric phosphate crystals as a site; while the surface coated with polydopamine is equivalent to being closed, and it is difficult to grow ferric phosphate as a site; since the growth speed of the surface coated with polydopamine and the surface of anhydrous ferric phosphate in the modified ferric phosphate seed crystal partially coated with polydopamine is inconsistent, thereby obtaining ferric phosphate particles with poor sphericity.

[0048] During the precipitation reaction process, the present invention simultaneously adds modified iron phosphate seeds and small-particle iron phosphate seeds, so that they grow in a mixed solution of a phosphorus source and an iron salt to form large-particle iron phosphate and small-particle iron phosphate. The modified iron phosphate seeds grow into large-particle iron phosphate with low sphericity uniformity, and the small-particle iron phosphate seeds grow into iron phosphate with high sphericity uniformity because they are not modified, thereby obtaining an iron phosphate material with large and small particle grading by a one-step method. The iron phosphate material is further mixed and calcined with a lithium source to obtain a lithium iron phosphate material with a bimodal distribution and a sphericity difference of large-particle lithium iron phosphate greater than that of small-particle lithium iron phosphate.

[0049] In some embodiments, the preparation method of large-particle iron phosphate seeds partially coated with polydopamine includes: mixing and dispersing large-particle iron phosphate seeds and a surfactant in a Tris-HCl buffer solution containing dopamine hydrochloride, stirring the reaction, filtering, washing, and drying to obtain large-particle iron phosphate seeds partially coated with polydopamine.

[0050] The present invention adopts the above method to prepare large-size iron phosphate seeds partially coated with polydopamine, and obtains large-size iron phosphate seeds partially coated with polydopamine whose surface is partially covered with polydopamine by controlling the concentration of components.

[0051] In some embodiments, the phosphorus source includes at least one of ammonium phosphate, diammonium phosphate, monoammonium phosphate, sodium monohydrogen phosphate, and sodium dihydrogen phosphate.

[0052] In some embodiments, the iron salt includes at least one of ferric chloride, ferric nitrate, and ferric sulfate.

[0053] In some embodiments, the carbon source includes at least one of sucrose, glucose, starch, dopamine, and polyethylene glycol.

[0054] In some embodiments, the lithium source is at least one of lithium hydroxide, lithium carbonate, and lithium nitrate.

[0055] In some embodiments, the mass ratio of the carbon source content to the ferric phosphate material is 0.05-0.15:1 (the mass ratio of the carbon source content to the ferric phosphate material can be 0.05, 0.08, 0.10, 0.12, 0.14, 0.15 or any value in the range of 0.05-0.15).

[0056] In some embodiments, the calcination temperature is 700-850°C (the calcination temperature can be 700°C, 725°C, 750°C, 775°C, 800°C, 825°C, 850°C or any value between 700-850°C), and the time is 20-35h (the time can be 20h, 22h, 25h, 27h, 30h, 32h, 35h or any value between 20-35h).

[0057] In some embodiments, the surfactant is at least one of anionic surfactants, including at least one of sodium dodecylbenzene sulfonate (SDBS), sodium fatty alcohol ether sulfate (AES) and sodium stearate methyl polyoxyethylene ether sulfonate (FMES); the addition of the surfactant can prevent the agglomeration of large-particle iron phosphate seeds, which is conducive to the generation of large-particle iron phosphate seeds partially coated with polydopamine with a target coating morphology.

[0058] In some embodiments, the concentration of the surfactant in the Tris-HCl buffer solution is 0.1-3 g / L (the concentration of the surfactant in the Tris-HCl buffer solution can be 0.1 g / L, 0.5 g / L, 1.0 g / L, 1.5 g / L, 2.0 g / L, 2.5 g / L, 3.0 g / L or any value between 0.1-3 g / L).

[0059] In some embodiments, the mass ratio of large particle size iron phosphate seeds and surfactant is 50:1-5 (the mass ratio of large particle size iron phosphate seeds and surfactant can be 50:1, 50:2, 50:3, 50:4, 50:5 or any value in the range of 50:1-5).

[0060] In some embodiments, the particle size of the large-particle iron phosphate seed crystals is 400-1500 nm (the particle size of the large-particle iron phosphate seed crystals can be any value of 400-500 nm, 600-700 nm, 700-800 nm, 800-900 nm, 900-1000 nm, 1000-1100 nm, 1100-1200 nm, 1200-1300 nm, 1300-1400 nm, 1400-1500 nm or 400-1500 nm); by controlling the particle size of the large-particle iron phosphate seed crystals, D b The value of D b The value of varies with the particle size of the large-particle iron phosphate seeds.

[0061] In some embodiments, the particle size of the small-particle iron phosphate seed crystals is 200-600 nm (the particle size of the small-particle iron phosphate seed crystals can be any value in the range of 200-300 nm, 300-400 nm, 400-500 nm, 500-600 nm or 200-600 nm); the D f The value of D f The value of varies with the particle size of the small-particle iron phosphate seeds.

[0062] In some embodiments, the pH of the Tris-HCl buffer solution is 8-8.5 (the pH of the Tris-HCl buffer solution may be 8, 8.1, 8.2, 8.3, 8.4, 8.5 or any value between 8 and 8.5).

[0063] In some embodiments, the concentration of dopamine hydrochloride in Tris-HCl buffer solution is 0.1-0.3 mg / mL (eg, 0.1 mg / mL, 0.15 mg / mL, 0.2 mg / mL, 0.25 mg / mL, 0.3 mg / mL, or any value between 0.1-0.3 mg / mL).

[0064] The present invention controls the concentration of dopamine hydrochloride to control the coating amount of polydopamine on the large-particle iron phosphate seed crystals partially coated with polydopamine, thereby affecting the sample standard deviation σ of the circularity C of the large-particle lithium iron phosphate b Specifically, within the specified range, as the concentration of dopamine hydrochloride increases σ b The bigger.

[0065] In some embodiments, the temperature of vacuum dehydration is 160-190°C (the temperature of vacuum dehydration can be 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C or any value between 160 and 190°C), and the time is 1-1.5h (the time can be 1h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h or any value between 1-1.5h).

[0066] At this temperature, ferric phosphate dihydrate can remove crystal water to obtain anhydrous ferric phosphate. The present invention controls the thickness of anhydrous ferric phosphate formed by dehydration of the surface layer of the modified ferric phosphate seed crystal by controlling the vacuum dehydration time and temperature, thereby affecting the sphericity of the large-particle ferric phosphate obtained. Specifically, the higher the vacuum dehydration temperature and the longer the time, the greater the thickness of the anhydrous ferric phosphate, the lower the circularity of the large-particle ferric phosphate obtained by the precipitation reaction, and the σ of the large-particle lithium iron phosphate obtained by subsequent calcination with the lithium source. b On the contrary, the lower the vacuum dehydration temperature and the shorter the time, the larger the σ of the obtained large-particle lithium iron phosphate b The smaller.

[0067] In some embodiments, the volume ratio of modified ferric phosphate seeds to small particle size ferric phosphate seeds is 0.9-1.5:1 (the volume ratio of modified ferric phosphate seeds to small particle size ferric phosphate seeds can be 0.9:1, 1.0:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1 or any value in the range of 0.9-1.5:1).

[0068] In some embodiments, the volume ratio of the total volume of the modified iron phosphate seeds and the small particle size iron phosphate seeds to water is 1:4-12 (the volume ratio of the total volume of the modified iron phosphate seeds and the small particle size iron phosphate seeds to water can be 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12 or any value of 1:4-12).

[0069] The present invention affects V by controlling the volume ratio of the modified ferric phosphate seed crystals to the small-particle-size ferric phosphate seed crystals. b / V f , V b / V f It increases with the volume ratio of modified ferric phosphate seeds to small particle size ferric phosphate seeds.

[0070] In some embodiments, the concentration of the iron salt in water is 0.5-1.2 mol / L (the concentration of the iron salt in water can be 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 1.1 mol / L, 1.2 mol / L or any value between 0.5-1.2 mol / L).

[0071] In some embodiments, the molar ratio of the iron element of the iron salt to the phosphorus element of the phosphorus source is 1:1-1.5 (the molar ratio of the iron element of the iron salt to the phosphorus element of the phosphorus source can be 1:1, 1:1.2, 1:1.3, 1:1.4, 1:1.5 or any value of 1:1-1.5).

[0072] The molar ratio of iron and phosphorus in the liquid phase during the precipitation reaction will affect the particle size distribution (span) of the lithium iron phosphate material. As the iron-phosphorus ratio decreases, the particle size distribution becomes wider.

[0073] In some embodiments, the stirring rate of the precipitation reaction is 350-750 rpm (the stirring rate of the precipitation reaction can be 350 rpm, 400 rpm, 450 rpm, 500 rpm, 550 rpm, 600 rpm, 650 rpm, 700 rpm, 750 rpm or any value in the range of 350-750 rpm); as the stirring rate increases, the particle size of the lithium iron phosphate material becomes smaller.

[0074] A third aspect of the present invention provides a positive electrode plate, comprising a positive electrode collector and a positive electrode material layer disposed on the positive electrode collector and comprising a positive electrode active material. The positive electrode material layer can be disposed on one surface of the positive electrode collector or on both surfaces of the positive electrode collector.

[0075] Wherein, the positive electrode active material includes the lithium iron phosphate material provided by the first aspect of the present invention, or the lithium iron phosphate material obtained by the preparation method provided by the second aspect of the present invention.

[0076] The present invention further provides a secondary battery, the secondary battery comprising a positive electrode sheet, a negative electrode sheet and a separator, wherein the positive electrode sheet comprises the positive electrode sheet provided in the third aspect of the present invention.

[0077] [Negative electrode] In the secondary battery of the present invention, the negative electrode plate may include a negative electrode current collector and a negative electrode material layer disposed on the negative electrode current collector and including a negative electrode active material. The negative electrode material layer may be disposed on one surface of the negative electrode current collector or on both surfaces of the negative electrode current collector.

[0078] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0079] In some embodiments, the negative electrode active material may be a negative electrode active material for a secondary battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: graphite (e.g., artificial graphite, natural graphite), soft carbon, hard carbon, mesophase carbon microspheres, carbon fibers, carbon nanotubes, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may be selected from at least one of elemental silicon, silicon oxides, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxides, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for secondary batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0080] [Electrolytes] The electrolyte plays a role in conducting ions between the positive electrode and the negative electrode. The present invention has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be selected from an electrolyte. The electrolyte includes an electrolyte salt and a solvent.

[0081] In some embodiments, the electrolyte salt can be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0082] In some embodiments, the solvent can be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).

[0083] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain properties of the secondary battery, such as additives that improve the overcharge performance of the secondary battery, additives that improve the high temperature performance of the secondary battery, and additives that improve the low temperature performance of the secondary battery.

[0084] [Isolation film] In the secondary battery of the present invention, the isolation membrane is arranged between the positive electrode sheet and the negative electrode sheet to play an isolating role. The type of the isolation membrane is not specifically limited, and any known porous structure isolation membrane with good chemical stability and mechanical stability can be selected. In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without special restrictions. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without special restrictions.

[0085] The positive electrode sheet, the negative electrode sheet and the isolation film can be made into an electrode assembly through a lamination process or a winding process, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolation role; the electrode assembly is placed in an outer package, the electrolyte is injected and sealed, and a lithium-ion battery can be obtained.

[0086] The outer packaging of the lithium-ion battery is used to encapsulate the electrode assembly and the electrolyte. In some embodiments, the outer packaging of the lithium-ion battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the lithium-ion battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.

[0087] The present invention has no particular limitation on the shape of the lithium-ion battery, which may be cylindrical, square or any other shape.

[0088] In some embodiments, lithium-ion batteries can be assembled into a secondary battery module. The number of lithium-ion batteries contained in the secondary battery module can be multiple, and the specific number can be adjusted according to the application and capacity of the secondary battery module.

[0089] In some embodiments, the secondary battery modules described above may also be assembled into a secondary battery pack, and the number of secondary battery modules contained in the secondary battery pack may be adjusted according to the application and capacity of the secondary battery pack.

[0090] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0091] The features and properties of the present invention are further described in detail below in conjunction with the examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention.

[0092] Embodiment 1: (1) Preparation of large-particle iron phosphate seeds partially coated with polydopamine: large-particle iron phosphate seeds with a particle size of 800-900 nm and sodium dodecylbenzene sulfonate were dispersed in a Tris-HCl buffer solution with a dopamine hydrochloride concentration of 0.2 mg / mL by ultrasonic treatment in a mass ratio of 25:1. After continuous stirring at a speed of 750 rpm for 24 h, the large-particle iron phosphate seeds partially coated with polydopamine were obtained by filtering, washing and drying. The concentration of sodium dodecylbenzene sulfonate in the buffer solution was 1.8 g / L, and the pH value of the Tris-HCl buffer solution was 8.5. Drying was performed at 80°C for 6 h.

[0093] (2) Preparation of modified iron phosphate seed crystals: The large-particle iron phosphate seed crystals partially coated with polydopamine were vacuum dehydrated at 185° C. for 1.5 h to obtain modified iron phosphate seed crystals.

[0094] (3) Preparation of iron phosphate material: Disperse modified iron phosphate seeds and small-particle iron phosphate seeds with a particle size of 200-300 nm in deionized water at a volume ratio of 1.2:1, then add ferric chloride solution and diammonium hydrogen phosphate solution, and carry out precipitation reaction at a rotation speed of 650 rpm for 6 hours, then transfer to a phosphoric acid solution for aging for 4 hours, filter, wash, dry and calcine to obtain an iron phosphate material; The volume ratio of the total volume of the modified ferric phosphate seeds and the small-particle ferric phosphate seeds to deionized water is 1:8; during the precipitation reaction, the amount of ferric chloride solution added is controlled to maintain the concentration of iron ions in the reaction solution at 1 mol / L; during the precipitation reaction, the amount of diammonium hydrogen phosphate solution added is controlled to maintain the concentration of phosphorus in the reaction solution at 1.1 mol / L; and ammonia water is used to control the pH of the reaction solution to 1.5.

[0095] (4) Preparation of lithium iron phosphate material: The iron phosphate material, lithium hydroxide, glucose and ethanol are mixed and ground to obtain a slurry; the slurry is dried and ground, and then calcined at 750°C for 20 hours to obtain a lithium iron phosphate material; the molar ratio of iron element to lithium element in the slurry is 1:1.03, the mass ratio of glucose to iron phosphate material is 0.05:1, and the solid content of the slurry is 35wt%.

[0096] Embodiment 2: The difference between this embodiment and embodiment 1 is that: In step (1) of preparing large-size iron phosphate seed crystals partially coated with polydopamine: replace "the concentration of dopamine hydrochloride is 0.2 mg / mL" with "the concentration of dopamine hydrochloride is 0.1 mg / mL"; In step (2) of preparing modified iron phosphate seed crystals: “dehydrate the large-particle iron phosphate seed crystals partially coated with polydopamine under vacuum at 185° C. for 1.5 h to obtain modified iron phosphate seed crystals” is replaced with “dehydrate the large-particle iron phosphate seed crystals partially coated with polydopamine under vacuum at 160° C. for 1 h to obtain modified iron phosphate seed crystals”; In the process of preparing the iron phosphate material in step (3): replace “transferred to a phosphoric acid solution and aged for 4 hours” with “transferred to a phosphoric acid solution and aged for 6 hours”.

[0097] Embodiment 3: The difference between this embodiment and embodiment 1 is that: In step (1) of preparing large-size iron phosphate seed crystals partially coated with polydopamine: replace "the concentration of dopamine hydrochloride is 0.2 mg / mL" with "the concentration of dopamine hydrochloride is 0.3 mg / mL"; In step (2) of preparing modified iron phosphate seed crystals: “dehydrate the large-particle iron phosphate seed crystals partially coated with polydopamine under vacuum at 185° C. for 1.5 h to obtain modified iron phosphate seed crystals” is replaced with “dehydrate the large-particle iron phosphate seed crystals partially coated with polydopamine under vacuum at 190° C. for 1.5 h to obtain modified iron phosphate seed crystals”; In the process of preparing the iron phosphate material in step (3): replace “transferred to a phosphoric acid solution and aged for 4 hours” with “transferred to a phosphoric acid solution and aged for 3 hours”.

[0098] Embodiment 4: The difference between this embodiment and embodiment 1 is that: Replace the process of “step (3) preparing iron phosphate material” with “(3) preparing iron phosphate material: dispersing modified iron phosphate seed crystals and small-size iron phosphate seed crystals with a particle size of 200-300 nm in deionized water at a volume ratio of 0.9:1, then adding ferric chloride solution and diammonium hydrogen phosphate solution, and carrying out precipitation reaction at a rotation speed of 750 rpm for 6 h, then transferring to a phosphoric acid solution for aging for 5 h, filtering, washing, drying and roasting to obtain an iron phosphate material; The volume ratio of the total volume of the modified iron phosphate seed crystals and the small-size iron phosphate seed crystals with a particle size of 200-300 nm to the volume of deionized water is 1:10; During the precipitation reaction, the amount of ferric chloride solution added was controlled to maintain the concentration of iron ions at 1.1 mol / L; during the precipitation reaction, the amount of diammonium hydrogen phosphate solution added was controlled to maintain the concentration of phosphorus in the solution at 1.43 mol / L. ” Embodiment 5: (1) Preparation of large-particle iron phosphate seeds partially coated with polydopamine: large-particle iron phosphate seeds with a particle size of 500-600 nm and sodium dodecylbenzene sulfonate were dispersed in a Tris-HCl buffer solution containing 0.1 mg / mL dopamine hydrochloride by ultrasonic treatment in a mass ratio of 25:1. After continuous stirring at a speed of 1000 rpm for 24 h, the mixture was filtered, washed, and dried to obtain large-particle iron phosphate seeds partially coated with polydopamine; the concentration of sodium dodecylbenzene sulfonate in the buffer solution was 2.2 g / L, and the pH value of the Tris-HCl buffer solution was 8.5; the drying step was drying at 80°C for 6 h.

[0099] (2) Preparation of modified iron phosphate seed crystals: The large-particle iron phosphate seed crystals partially coated with polydopamine were vacuum dehydrated at 185° C. for 1.5 h to obtain modified iron phosphate seed crystals.

[0100] (3) Preparation of iron phosphate material: Disperse modified iron phosphate seeds and small-particle iron phosphate seeds with a particle size of 200-300 nm in deionized water at a volume ratio of 1.2:1, then add ferric chloride solution and diammonium hydrogen phosphate solution, and perform precipitation reaction at a rotation speed of 600 rpm for 6 hours, then transfer to a phosphoric acid solution for aging for 6 hours, filter, wash, dry, and calcine to obtain an iron phosphate material; The volume ratio of the total volume of the modified iron phosphate seed crystals and the small-size iron phosphate seed crystals with a particle size of 200-300 nm to the volume of deionized water is 1:8; During the precipitation reaction, the amount of ferric chloride solution added was controlled to maintain the concentration of iron ions at 0.9 mol / L; during the precipitation reaction, the amount of diammonium hydrogen phosphate solution added was controlled to maintain the concentration of phosphorus in the solution at 0.99 mol / L. (4) Preparation of lithium iron phosphate material: The iron phosphate material, lithium hydroxide, glucose and ethanol are mixed and ground to obtain a slurry; the slurry is dried and ground, and then calcined at 750°C for 20 hours to obtain a lithium iron phosphate material; the molar ratio of iron element to lithium element in the slurry is 1:1.03, the mass ratio of glucose to iron phosphate material is 0.05:1, and the solid content of the slurry is 35wt%.

[0101] Embodiment 6: The difference between this embodiment and embodiment 1 is that: In step (3) of preparing the iron phosphate material: "dispersing the modified iron phosphate seed crystals and the small-particle iron phosphate seed crystals with a particle size of 200-300 nm in deionized water at a volume ratio of 1.2:1" is replaced with "dispersing the modified iron phosphate seed crystals and the small-particle iron phosphate seed crystals with a particle size of 200-300 nm in deionized water at a volume ratio of 1.5:1"; Replace "precipitation reaction at a rotation speed of 650 rpm for 6 hours" with "precipitation reaction at a rotation speed of 400 rpm for 6 hours"; Replace “During the precipitation reaction, the amount of diammonium hydrogen phosphate solution added was controlled to maintain the concentration of phosphorus in the solution at 1.1 mol / L” with “During the precipitation reaction, the amount of diammonium hydrogen phosphate solution added was controlled to maintain the concentration of phosphorus in the solution at 1.5 mol / L”.

[0102] Embodiment 7: The difference between this embodiment and embodiment 1 is that: In step (3) of preparing the iron phosphate material: "dispersing the modified iron phosphate seed crystals and the small-particle iron phosphate seed crystals with a particle size of 200-300 nm in deionized water at a volume ratio of 1.2:1" is replaced with "dispersing the modified iron phosphate seed crystals and the small-particle iron phosphate seed crystals with a particle size of 200-300 nm in deionized water at a volume ratio of 0.9:1"; Replace "precipitation reaction at a rotation speed of 650 rpm for 6 hours" with "precipitation reaction at a rotation speed of 750 rpm for 6 hours"; Replace “During the precipitation reaction, the amount of diammonium hydrogen phosphate solution added was controlled to maintain the concentration of phosphorus in the solution at 1.1 mol / L” with “During the precipitation reaction, the amount of diammonium hydrogen phosphate solution added was controlled to maintain the concentration of phosphorus in the solution at 1.3 mol / L”.

[0103] Embodiment 8: The difference between this embodiment and embodiment 1 is that: In the process of preparing large-particle iron phosphate seeds partially coated with polydopamine in step (1): "Using ultrasonic treatment, large-particle iron phosphate seeds with a particle size of 800-900 nm and sodium dodecylbenzene sulfonate are dispersed in a Tris-HCl buffer solution with a dopamine hydrochloride concentration of 0.2 mg / mL in a mass ratio of 25:1, and after continuous stirring at a speed of 750 rpm for 24 hours, the large-particle iron phosphate seeds partially coated with polydopamine are obtained by filtering, washing and drying; sodium dodecylbenzene sulfonate is dispersed in a Tris-HCl buffer solution with a particle size of 800-900 nm in a mass ratio of 25:1, and after continuous stirring at a speed of 750 rpm for 24 hours, the large-particle iron phosphate seeds partially coated with polydopamine are obtained by filtering, washing and drying; The concentration in the solution is 1.8 g / L" is replaced by "Using ultrasonic treatment, large-particle iron phosphate seeds with a particle size of 1300-1400 nm and sodium dodecylbenzene sulfonate are dispersed in a Tris-HCl buffer solution with a dopamine hydrochloride concentration of 0.2 mg / mL in a mass ratio of 25:1, and after continuous stirring at a speed of 750 rpm for 24 hours, the large-particle iron phosphate seeds partially coated with polydopamine are obtained by filtering, washing and drying; the concentration of sodium dodecylbenzene sulfonate in the buffer solution is 0.9 g / L"; In the process of preparing the iron phosphate material in step (3): "precipitation reaction at a rotation speed of 650 rpm for 6 hours, and then transferred to a phosphoric acid solution for aging for 4 hours" is replaced with "precipitation reaction at a rotation speed of 500 rpm for 6 hours, and then transferred to a phosphoric acid solution for aging for 7 hours"; Replace “During the precipitation reaction, the amount of diammonium hydrogen phosphate solution added was controlled to maintain the concentration of phosphorus in the solution at 1.1 mol / L” with “During the precipitation reaction, the amount of diammonium hydrogen phosphate solution added was controlled to maintain the concentration of phosphorus in the solution at 1.5 mol / L”.

[0104] Embodiment 9: The difference between this embodiment and embodiment 1 is that: Replace “step (3) preparing iron phosphate material” with “dispersing modified iron phosphate seeds and small-size iron phosphate seeds with a particle size of 500-600 nm in deionized water at a volume ratio of 1.2:1, then adding ferric chloride solution and diammonium hydrogen phosphate solution, and carrying out precipitation reaction at a rotation speed of 700 rpm for 6 hours, then transferring to a phosphoric acid solution for aging for 4 hours, filtering, washing, drying and roasting to obtain an iron phosphate material; The volume ratio of the total volume of the modified iron phosphate seed crystals and the small-size iron phosphate seed crystals with a particle size of 500-600 nm to the volume of deionized water is 1:8; During the precipitation reaction, the amount of ferric chloride solution added was controlled to maintain the concentration of iron ions at 1 mol / L; during the precipitation reaction, the amount of diammonium hydrogen phosphate solution added was controlled to maintain the concentration of phosphorus in the solution at 1.3 mol / L. Embodiment 10: The difference between this embodiment and embodiment 1 is that: In step (1) of preparing large-size iron phosphate seed crystals partially coated with polydopamine: replacing "sodium dodecylbenzene sulfonate" with "sodium fatty alcohol ether sulfate"; Replace the process of “step (3) preparing iron phosphate material” with “(3) preparing iron phosphate material: dispersing modified iron phosphate seed crystals and small-size iron phosphate seed crystals with a particle size of 200-300 nm in deionized water at a volume ratio of 1.4:1, then adding ferric chloride solution and diammonium hydrogen phosphate solution, and carrying out precipitation reaction at a rotation speed of 750 rpm for 6 hours, then transferring to a phosphoric acid solution for aging for 6 hours, filtering, washing, drying and roasting to obtain an iron phosphate material; The volume ratio of the total volume of the modified iron phosphate seed crystals and the small-size iron phosphate seed crystals with a particle size of 200-300 nm to the volume of deionized water is 1:12; During the precipitation reaction, the amount of ferric chloride solution added was controlled to maintain the concentration of iron ions at 1.2 mol / L; during the precipitation reaction, the amount of diammonium hydrogen phosphate solution added was controlled to maintain the concentration of phosphorus in the solution at 1.68 mol / L. Embodiment 11: The difference between this embodiment and embodiment 1 is that: In step (1) of preparing large-size iron phosphate seed crystals partially coated with polydopamine: replacing "sodium dodecylbenzene sulfonate" with "sodium fatty alcohol ether sulfate"; Replace the process of “step (3) preparing iron phosphate material” with “(3) preparing iron phosphate material: dispersing modified iron phosphate seed crystals and small-size iron phosphate seed crystals with a particle size of 200-300 nm in deionized water at a volume ratio of 1.1:1, then adding ferric chloride solution and diammonium hydrogen phosphate solution, and carrying out precipitation reaction at a rotation speed of 600 rpm for 6 h, then transferring to a phosphoric acid solution for aging for 5 h, filtering, washing, drying and roasting to obtain an iron phosphate material; The volume ratio of the total volume of the modified iron phosphate seed crystals and the small-size iron phosphate seed crystals with a particle size of 200-300 nm to the volume of deionized water is 1:7; During the precipitation reaction, the amount of ferric chloride solution added was controlled to maintain the concentration of iron ions at 0.8 mol / L; during the precipitation reaction, the amount of diammonium hydrogen phosphate solution added was controlled to maintain the concentration of phosphorus in the solution at 0.88 mol / L. Embodiment 12: (1) Preparation of large-particle iron phosphate seeds partially coated with polydopamine: large-particle iron phosphate seeds with a particle size of 1200-1300 nm and sodium dodecylbenzene sulfonate were dispersed in a Tris-HCl buffer solution with a dopamine hydrochloride concentration of 0.12 mg / mL by ultrasonic treatment, and the mixture was continuously stirred at 650 rpm for 24 h, filtered, washed, and dried to obtain large-particle iron phosphate seeds partially coated with polydopamine; the concentration of sodium dodecylbenzene sulfonate in the buffer solution was 2.6 g / L, and the pH value of the Tris-HCl buffer solution was 8.0; and drying was performed at 80°C for 6 h.

[0105] (2) Preparation of modified iron phosphate seed crystals: The large-particle iron phosphate seed crystals partially coated with polydopamine were vacuum dehydrated at 185° C. for 1.5 h to obtain modified iron phosphate seed crystals.

[0106] (3) Preparation of iron phosphate material: Disperse modified iron phosphate seed crystals and small-particle iron phosphate seed crystals with a particle size of 400-500 nm in deionized water at a volume ratio of 1:1, then add ferric chloride solution and diammonium hydrogen phosphate solution, and perform precipitation reaction at a rotation speed of 400 rpm for 6 hours, then transfer to a phosphoric acid solution for aging for 4 hours, filter, wash, dry, and calcine to obtain an iron phosphate material; The volume ratio of the total volume of the modified iron phosphate seed crystals and the small-size iron phosphate seed crystals with a particle size of 400-500 nm to the volume of deionized water is 1:6; During the precipitation reaction, the amount of ferric chloride solution added was controlled to maintain the concentration of iron ions at 0.6 mol / L; during the precipitation reaction, the amount of diammonium hydrogen phosphate solution added was controlled to maintain the concentration of phosphorus in the solution at 0.66 mol / L. (4) Preparation of lithium iron phosphate material: The iron phosphate material, lithium hydroxide, glucose and ethanol are mixed and ground to obtain a slurry; the slurry is dried and ground, and then calcined at 750°C for 20 hours to obtain a lithium iron phosphate material; the molar ratio of iron element to lithium element in the slurry is 1:1.01, the mass ratio of glucose to iron phosphate material is 0.05:1, and the solid content of the slurry is 35wt%.

[0107] Embodiment 13: (1) Preparation of large-particle iron phosphate seeds partially coated with polydopamine: Using ultrasonic treatment, large-particle iron phosphate seeds with a particle size of 800-900 nm and sodium dodecylbenzene sulfonate are dispersed in a Tris-HCl buffer solution with a dopamine hydrochloride concentration of 0.2 mg / mL in a mass ratio of 35:1. After continuous stirring at a speed of 500 rpm for 24 hours, the mixture is filtered, washed, and dried to obtain large-particle iron phosphate seeds partially coated with polydopamine; the concentration of sodium dodecylbenzene sulfonate in the buffer solution is 2.6 g / L, and the pH value of the Tris-HCl buffer solution is 8.5; and the drying is performed at a temperature of 80°C for 6 hours.

[0108] (2) Preparation of modified iron phosphate seed crystals: The large-particle iron phosphate seed crystals partially coated with polydopamine were vacuum dehydrated at 185° C. for 1.5 h to obtain modified iron phosphate seed crystals.

[0109] (3) Preparation of iron phosphate material: Disperse modified iron phosphate seeds and small-particle iron phosphate seeds with a particle size of 200-300 nm in deionized water at a volume ratio of 0.9:1, then add ferric chloride solution and diammonium hydrogen phosphate solution, and carry out precipitation reaction at a rotation speed of 750 rpm for 6 hours, then transfer to a phosphoric acid solution for aging for 4 hours, filter, wash, dry and calcine to obtain an iron phosphate material; The volume ratio of the total volume of the modified iron phosphate seed crystals and the small-size iron phosphate seed crystals with a particle size of 200-300 nm to the volume of deionized water is 1:12; During the precipitation reaction, the amount of ferric chloride solution added was controlled to maintain the concentration of iron ions at 1.2 mol / L; during the precipitation reaction, the amount of diammonium hydrogen phosphate solution added was controlled to maintain the concentration of phosphorus in the solution at 1.56 mol / L. (4) Preparation of lithium iron phosphate material: The iron phosphate material, lithium hydroxide, glucose and ethanol are mixed and ground to obtain a slurry; the slurry is dried and ground, and then calcined at 750°C for 20 hours to obtain a lithium iron phosphate material; the molar ratio of iron element to lithium element in the slurry is 1:1.01, the mass ratio of glucose to iron phosphate material is 0.05:1, and the solid content of the slurry is 35wt%.

[0110] Embodiment 14: (1) Preparation of large-particle iron phosphate seeds partially coated with polydopamine: large-particle iron phosphate seeds with a particle size of 500-600 nm and sodium dodecylbenzene sulfonate were dispersed in a Tris-HCl buffer solution with a dopamine hydrochloride concentration of 0.1 mg / mL by ultrasonic treatment, and the mixture was continuously stirred at 750 rpm for 24 h, filtered, washed, and dried to obtain large-particle iron phosphate seeds partially coated with polydopamine; the concentration of sodium dodecylbenzene sulfonate in the buffer solution was 2.0 g / L, and the pH value of the Tris-HCl buffer solution was 8.5; and drying was performed at 80°C for 6 h.

[0111] (2) Preparation of modified iron phosphate seed crystals: The large-particle iron phosphate seed crystals partially coated with polydopamine were vacuum dehydrated at 185° C. for 1.5 h to obtain modified iron phosphate seed crystals.

[0112] (3) Preparation of iron phosphate material: Disperse modified iron phosphate seeds and small-particle iron phosphate seeds with a particle size of 200-300 nm in deionized water at a volume ratio of 1.5:1, then add ferric chloride solution and diammonium hydrogen phosphate solution, and perform precipitation reaction at a rotation speed of 500 rpm for 6 hours, then transfer to a phosphoric acid solution for aging for 4 hours, filter, wash, dry, and calcine to obtain an iron phosphate material; The volume ratio of the total volume of the modified iron phosphate seed crystals and the small-size iron phosphate seed crystals with a particle size of 200-300 nm to the volume of deionized water is 1:5; During the precipitation reaction, the amount of ferric chloride solution added was controlled to maintain the concentration of iron ions at 0.7 mol / L; during the precipitation reaction, the amount of diammonium hydrogen phosphate solution added was controlled to maintain the concentration of phosphorus in the solution at 0.77 mol / L. (4) Preparation of lithium iron phosphate material: The iron phosphate material, lithium hydroxide, glucose and ethanol are mixed and ground to obtain a slurry; the slurry is dried and ground, and then calcined at 750°C for 20 hours to obtain a lithium iron phosphate material; the molar ratio of iron element to lithium element in the slurry is 1:1.02, the mass ratio of glucose to iron phosphate material is 0.05:1, and the solid content of the slurry is 35wt%.

[0113] Embodiment 15: (1) Preparation of large-particle iron phosphate seeds partially coated with polydopamine: large-particle iron phosphate seeds with a particle size of 1100-1200 nm and sodium dodecylbenzene sulfonate were dispersed in a Tris-HCl buffer solution with a dopamine hydrochloride concentration of 0.2 mg / mL by ultrasonic treatment, and the mixture was continuously stirred at a speed of 600 rpm for 24 h, filtered, washed, and dried to obtain large-particle iron phosphate seeds partially coated with polydopamine; the concentration of sodium dodecylbenzene sulfonate in the buffer solution was 1.2 g / L, and the pH value of the Tris-HCl buffer solution was 8.5; and drying was performed at 80°C for 6 h.

[0114] (2) Preparation of modified iron phosphate seed crystals: The large-particle iron phosphate seed crystals partially coated with polydopamine were vacuum dehydrated at 185° C. for 1.5 h to obtain modified iron phosphate seed crystals.

[0115] (3) Preparation of iron phosphate material: Disperse modified iron phosphate seeds and small-particle iron phosphate seeds with a particle size of 500-600 nm in deionized water at a volume ratio of 1.4:1, then add ferric chloride solution and diammonium hydrogen phosphate solution, and perform precipitation reaction at a rotation speed of 600 rpm for 6 hours, then transfer to a phosphoric acid solution for aging for 6 hours, filter, wash, dry, and calcine to obtain an iron phosphate material; The volume ratio of the total volume of the modified iron phosphate seed crystals and the small-size iron phosphate seed crystals with a particle size of 500-600 nm to the volume of deionized water is 1:7; During the precipitation reaction, the amount of ferric chloride solution added was controlled to maintain the concentration of iron ions at 0.8 mol / L; during the precipitation reaction, the amount of diammonium hydrogen phosphate solution added was controlled to maintain the concentration of phosphorus in the solution at 1.12 mol / L. (4) Preparation of lithium iron phosphate material: The iron phosphate material, lithium hydroxide, glucose and ethanol are mixed and ground to obtain a slurry; the slurry is dried and ground, and then calcined at 750°C for 20 hours to obtain a lithium iron phosphate material; the molar ratio of iron element to lithium element in the slurry is 1:1.01, the mass ratio of glucose to iron phosphate material is 0.05:1, and the solid content of the slurry is 35wt%.

[0116] Comparative Example 1: The difference between this comparative example and Example 1 is that: In step (1) of preparing large-size iron phosphate seed crystals partially coated with polydopamine: replace "the concentration of dopamine hydrochloride is 0.2 mg / mL" with "the concentration of dopamine hydrochloride is 0.4 mg / mL"; Replace “after continuous stirring at a rotation speed of 750 rpm for 24 h” with “after continuous stirring at a rotation speed of 500 rpm for 24 h”.

[0117] In step (2) of preparing modified iron phosphate seed crystals: "dehydrate the large-particle iron phosphate seed crystals partially coated with polydopamine under vacuum at 185° C. for 1.5 h to obtain modified iron phosphate seed crystals" is replaced with "dehydrate the large-particle iron phosphate seed crystals partially coated with polydopamine under vacuum at 195° C. for 2 h to obtain modified iron phosphate seed crystals"; Replace the process of “step (3) preparing iron phosphate material” with “(3) preparing iron phosphate material: dispersing modified iron phosphate seed crystals and small-size iron phosphate seed crystals with a particle size of 200-300 nm in deionized water at a volume ratio of 1.3:1, then adding ferric chloride solution and diammonium hydrogen phosphate solution, and carrying out precipitation reaction at a rotation speed of 400 rpm for 6 h, then transferring to a phosphoric acid solution for aging for 3 h, filtering, washing, drying and roasting to obtain an iron phosphate material; The volume ratio of the total volume of the modified iron phosphate seed crystals and the small-size iron phosphate seed crystals with a particle size of 200-300 nm to the volume of deionized water is 1:8; During the precipitation reaction, the amount of ferric chloride solution added was controlled to maintain the concentration of iron ions at 1 mol / L; during the precipitation reaction, the amount of diammonium hydrogen phosphate solution added was controlled to maintain the concentration of phosphorus in the solution at 1.1 mol / L. Comparative Example 2: (1) Preparation of modified iron phosphate seed crystals: Large-size iron phosphate seed crystals with a particle size of 800-900 nm were dried at 80° C. for 5 h, and then vacuum-dehydrated at 150° C. for 1 h to obtain modified iron phosphate seed crystals.

[0118] (2) Preparation of iron phosphate material: Disperse modified iron phosphate seeds and small-particle iron phosphate seeds with a particle size of 200-300 nm in deionized water at a volume ratio of 1.2:1, then add ferric chloride solution and diammonium hydrogen phosphate solution, and carry out precipitation reaction at a rotation speed of 650 rpm for 6 hours, then transfer to a phosphoric acid solution for aging for 4 hours, filter, wash, dry and calcine to obtain an iron phosphate material; The volume ratio of the total volume of the modified ferric phosphate seeds and the small-particle ferric phosphate seeds to deionized water is 1:8; during the precipitation reaction, the amount of ferric chloride solution added is controlled to maintain the concentration of iron ions in the reaction solution at 1 mol / L; during the precipitation reaction, the amount of diammonium hydrogen phosphate solution added is controlled to maintain the concentration of phosphorus in the reaction solution at 1.1 mol / L; and ammonia water is used to control the pH of the reaction solution to 1.5.

[0119] (3) Preparation of lithium iron phosphate material: The iron phosphate material, lithium hydroxide, glucose and ethanol are mixed and ground to obtain a slurry; the slurry is dried and ground, and then calcined at 750°C for 20 hours to obtain a lithium iron phosphate material; the molar ratio of iron element to lithium element in the slurry is 1:1.03, the mass ratio of glucose to iron phosphate material is 0.05:1, and the solid content of the slurry is 35wt%.

[0120] Comparative Example 3: The difference between this comparative example and comparative example 2 is only that: In the process of preparing modified ferric phosphate seed crystals in step (1), "further dehydrated under vacuum at 150° C. for 1 h" is replaced by "further dehydrated under vacuum at 200° C. for 1 h".

[0121] Comparative Example 4: (1) Preparation of iron phosphate material: large-particle iron phosphate seeds with a particle size of 800-900 nm and small-particle iron phosphate seeds with a particle size of 200-300 nm were dispersed in deionized water at a volume ratio of 1.2:1, and then ferric chloride solution and diammonium hydrogen phosphate solution were added. The precipitation reaction was carried out at a rotation speed of 650 rpm for 6 hours, and then the mixture was transferred to a phosphoric acid solution for aging for 4 hours. After filtering, washing, drying and calcining, the iron phosphate material was obtained; The volume ratio of the total volume of large-particle ferric phosphate seeds and small-particle ferric phosphate seeds to deionized water is 1:8; during the precipitation reaction, the amount of ferric chloride solution added is controlled to maintain the concentration of iron ions in the reaction solution at 1 mol / L; during the precipitation reaction, the amount of diammonium hydrogen phosphate solution added is controlled to maintain the concentration of phosphorus in the reaction solution at 1.1 mol / L; and ammonia water is used to control the pH of the reaction solution to 1.5.

[0122] (2) Preparation of lithium iron phosphate material: The iron phosphate material, lithium hydroxide, glucose and ethanol are mixed and ground to obtain a slurry; the slurry is dried and ground, and then calcined at 750°C for 20 hours to obtain a lithium iron phosphate material; the molar ratio of iron element to lithium element in the slurry is 1:1.03, the mass ratio of glucose to iron phosphate material is 0.05:1, and the solid content of the slurry is 35wt%.

[0123] Comparative Example 5: The difference between this comparative example and Example 1 is that: In step (1) of preparing large-size iron phosphate seed crystals partially coated with polydopamine: replace "the concentration of dopamine hydrochloride is 0.2 mg / mL" with "the concentration of dopamine hydrochloride is 0.4 mg / mL"; Replace “after stirring continuously at a rotation speed of 750 rpm for 24 h,” with “after stirring continuously at a rotation speed of 400 rpm for 24 h,”.

[0124] In the process of preparing modified ferric phosphate seed crystals in step (2), "the large-particle ferric phosphate seed crystals partially coated with polydopamine are vacuum dehydrated at 185°C for 1.5 h" is replaced by "the large-particle ferric phosphate seed crystals partially coated with polydopamine are vacuum dehydrated at 205°C for 1 h".

[0125] The lithium iron phosphate materials prepared in the above embodiments and comparative examples were tested, and the specific items and methods are as follows: 1. Particle size distribution: According to GB / T 19077-2016, the particle size distribution information of the lithium iron phosphate material prepared in each embodiment and comparative example was tested using a laser particle size analyzer. The test results of each embodiment and comparative example are shown in Table 1.

[0126] Figure 3 The particle size distribution diagram of the lithium iron phosphate material provided in Examples 4 and 5. It can be seen from the figure that compared with Example 4, the particle size distribution of the lithium iron phosphate material obtained in Example 5 is b and D f Smaller; V of Example 5 f Smaller, V b This indicates that the lithium iron phosphate material with target characteristics can be obtained by adjusting the preparation process parameters through the method of the present invention.

[0127] 2. Morphology characterization: The lithium iron phosphate samples of each embodiment and comparative example were tested using a scanning electron microscope. Figure 1 The SEM image of the lithium iron phosphate material provided in Example 1 shows the coexistence of lithium iron phosphate materials with better and worse circularity and larger particle size; Figure 2 The SEM image of the lithium iron phosphate material provided in Comparative Example 2 shows that the lithium iron phosphate material with large particle size has better sphericity.

[0128] 3. Circularity calculation method: By analyzing the SEM image using ImageJ, the specific steps are as follows: 1) Obtaining SEM images of analyzable lithium iron phosphate materials; 2) Using the “magic wand” tool in ImageJ, identify the boundaries of the particles in the SEM image and independently select the projection surface of each particle in the SEM image; 3) The area, perimeter and circularity C of the projection surface of each lithium iron phosphate particle in the SEM image were obtained by ImageJ analysis; 4) Obtain D according to the particle size distribution curve f and D b , and calculate the area of ​​the corresponding standard circle respectively to determine the standard for identifying large-particle lithium iron phosphate and small-particle lithium iron phosphate; the formula for the area of ​​the standard circle is: S=1 / 4×π×d 2 , where d is D f or D b ; Large particle lithium iron phosphate has a projected area greater than or equal to S max =1 / 4×π×D b 2 The projected area of ​​lithium iron phosphate particles is less than or equal to S min =1 / 4×π×D f2 Lithium iron phosphate particles; 5) Based on the data obtained in step 3) of the standard screening of large particle lithium iron phosphate and small particle lithium iron phosphate; 6) The data obtained by screening according to step 5) are calculated and the sample standard deviation of the circularity C of the large-particle lithium iron phosphate and the small-particle lithium iron phosphate is calculated.

[0129] The circularity calculation formula is: C = (4 × π × A) / P 2 , where A is the area of ​​the projection surface of the lithium iron phosphate particles, and P is the perimeter of the projection surface; the formula for the sample standard deviation is: , when calculating the sample standard deviation, the number of samples N must be at least 30, where C i is the circularity C of the i-th lithium iron phosphate particle, where 0.15≤C≤1.00, is the average circularity of N lithium iron phosphate particles.

[0130] The test results of each embodiment and comparative example are shown in Table 1.

[0131] 4. Tap density test: According to GB / T 5162-2006, the lithium iron phosphate materials of each embodiment and comparative example were tested using a tap density tester BT-302. The test results of each embodiment and comparative example are shown in Table 2.

[0132] 5. Specific surface area test: According to GB / T 19587-2004, the specific surface area of ​​the lithium iron phosphate material of each embodiment and comparative example was measured using a physical adsorption instrument. The test results of each embodiment and comparative example are shown in Table 2.

[0133] 6. Electrochemical performance test: Battery Assembly: A uniform slurry was prepared by mixing positive electrode material: acetylene black: PVDF at a mass ratio of 75:15:10 and evenly coated on an aluminum foil substrate as the positive electrode of the battery. A lithium sheet was used as the negative electrode of the simulated battery, a polypropylene porous membrane was used as the diaphragm, and the electrolyte was 1 mol LiPF6 dissolved in 1 L of a mixed solvent of ethylene carbonate (EC) and dimethyl carbonate (DMC) (volume ratio 1:1). The positive electrode, negative electrode, electrolyte, and diaphragm were assembled into a battery in an argon-protected glove box.

[0134] Steps for simulating battery rate testing: First, charge to 4.2V with constant current, then discharge to 2.0V with rate current, the released capacity is the discharge capacity at this rate, after discharge, discharge to 2.0V with constant current again, then test at the next rate. The discharge capacity of the battery at 0.1C, 1C and 5C is tested respectively, and the test results are shown in Table 2.

[0135] Table 1 Parameters of lithium iron phosphate materials

[0136] Table 2 Physical and electrochemical properties of lithium iron phosphate materials

[0137] It can be seen from Table 1-2 that the lithium iron phosphate materials of Examples 1-3 and Comparative Examples 1-5 have different σ b / σ f , as σ b / σ f As the tap density of the lithium iron phosphate material increases, the larger the BET is, the discharge specific capacity at 0.1C increases first and then decreases, and the capacity retention at 0.1C to 5C increases first and then decreases. Specifically, from Example 1, Example 2 and Comparative Example 2, as σ b / σ f The increase indicates that the morphological uniformity of large-particle lithium iron phosphate is reduced, which reduces the grading effect of lithium iron phosphate, so the tap density decreases. However, at the same time, the irregular large particles increase the BET, which increases the specific surface area of ​​the lithium iron phosphate material as a whole, which is beneficial to Li + The deintercalation of σ increases the specific capacity and rate. b / σ f Further increase, due to the low morphology uniformity of large-particle lithium iron phosphate, the tap density further decreases; at the same time, these irregular large particles further increase BET, but the irregular large particles increase the internal resistance of the battery, reducing the specific capacity and the capacity retention rate from 0.1C to 5C. b / σ f Lithium iron phosphate materials in the range of ≤5.00 have good specific capacity and rate performance.

[0138] From the examples 1, 4-5, 13-14, the In the preferred scope of the present invention, the Outside the preferred range of the present invention, it can be seen The lithium iron phosphate material within the preferred range has higher tap density and specific surface area, and therefore has better specific capacity and a capacity retention rate of 0.1C to 5C.

[0139] The lithium iron phosphate materials of Examples 1, 6 and 7 are only V b / V f The difference is large, as V b / V fAs the tap density of the lithium iron phosphate material increases, it first increases and then decreases, the BET gradually decreases, the 0.1C discharge specific capacity first increases and then decreases, and the capacity retention from 0.1C to 5C first increases and then decreases. Specifically, from Example 1 and Example 7, V b / V f Increase, indicating that the particle size is D b The proportion of large-particle lithium iron phosphate increases relatively, or the particle size is D f The proportion of small lithium iron phosphate particles is relatively reduced, so the tap density is increased and the specific surface area is reduced. However, due to the reduction in the proportion of small lithium iron phosphate particles, small particles are accumulated, thereby reducing the tortuous diffusion path formed by the accumulation, which is beneficial to Li + The diffusion of V ultimately leads to an increase in specific capacity and capacity retention from 0.1C to 5C. b / V f Further increase will reduce the grading effect of lithium iron phosphate, so the tap density decreases; at the same time, as the proportion of large-particle lithium iron phosphate increases, BET further decreases, which reduces the contact area of ​​the lithium iron phosphate material. At the same time, large particles increase the transmission path of lithium ions, so the specific capacity and the capacity retention rate from 0.1C to 5C are reduced.

[0140] The lithium iron phosphate materials of Examples 1, 8 and 9 are only D b / D f The difference is large, with D b / D f As the tap density increases, the BET increases first and then decreases, the specific capacity increases first and then decreases, and the capacity retention from 0.1C to 5C increases first and then decreases. Specifically, from Example 1 and Example 9, D b / D f The increase of lithium iron phosphate has a better grading effect and an increase in tap density, but the particle size of small lithium iron phosphate particles decreases, which has a greater impact on the increase of lithium iron phosphate BET. Therefore, the overall BET of lithium iron phosphate material increases, and thus the specific capacity and the capacity retention rate from 0.1C to 5C increase. From Example 8 and Example 1, D b / D f However, the increase in the particle size of large-particle lithium iron phosphate has a greater impact on the reduction of BET of lithium iron phosphate. Therefore, the overall BET of lithium iron phosphate material is reduced, and thus the specific capacity and the capacity retention rate from 0.1C to 5C are reduced.

[0141] The increase or decrease of span affects the tap density, BET and specific capacity of lithium iron phosphate materials, and the capacity retention rate from 0.1C to 5C, but the influence trend depends not only on the particle size of Dv10, Dv50, and Dv90, but also on their number. From Examples 10-11 and Example 1 of the present invention, only the span is different. As the span increases, the tap density and BET increase first and then decrease, so the specific capacity and the capacity retention rate from 0.1C to 5C also increase first and then decrease.

[0142] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A lithium iron phosphate material, characterized in that: The particle size distribution curve of the lithium iron phosphate material is a bimodal distribution, and the particle size distribution curve includes a first peak and a second peak in the positive direction of the horizontal axis, and the particle sizes corresponding to the first peak and the second peak are D f and D b , in μm; the corresponding volume percentages are V f and V b ; The lithium iron phosphate material satisfies 1.10≤σ b / σ f ≤5.00, where σ b is the sample standard deviation of the circularity C of large-particle lithium iron phosphate, σ f is the sample standard deviation of the circularity C of small-particle lithium iron phosphate, where C=(4×π×A) / P 2 , A is the projected area of ​​the lithium iron phosphate particles, and P is the perimeter of the projected area; The large-particle lithium iron phosphate has a projected area greater than or equal to S max =1 / 4×π×D b 2 The small lithium iron phosphate particles have a projected area less than or equal to S min =1 / 4×π×D f 2 of lithium iron phosphate particles.

2. The lithium iron phosphate material according to claim 1, characterized in that: The lithium iron phosphate material meets at least one of the following characteristics 1 and 2: Feature 1: The σ b Satisfy 0.05≤σ b ≤0.15; Feature 2: The σ f Satisfy 0.02≤σ f ≤0.

09.

3. The lithium iron phosphate material according to claim 1, characterized in that: The lithium iron phosphate material meets at least one of the following characteristics ad: Feature a: 0.3μm≤D f ≤1.0μm and 1.2μm≤D b ≤10μm; feature b: 3%≤V f ≤10% and 3%≤V b ≤10%; Characteristic c: 0.2 ≤ V b / V f ≤2.5; Characteristic d: 2.5 ≤ D b / D f ≤12.

4. The lithium iron phosphate material according to any one of claims 1 to 3, characterized in that: The lithium iron phosphate material meets the following requirements: ; Wherein, span satisfies 1.5≤span≤5, and span=(Dv90-Dv10) / Dv50, Dv90, Dv50 and Dv10 are the particle sizes corresponding to when the cumulative volume percentage of the lithium iron phosphate material reaches 90%, 50% and 10%, respectively, and the unit is μm.

5. A method for preparing the lithium iron phosphate material according to any one of claims 1 to 4, characterized in that: The preparation method comprises: The large-size iron phosphate seed crystals are coated with polydopamine to obtain large-size iron phosphate seed crystals partially coated with polydopamine; Dehydrating the large-size iron phosphate seed crystals partially coated with polydopamine under vacuum to obtain modified iron phosphate seed crystals; The modified ferric phosphate seed crystals and the small-size ferric phosphate seed crystals are mixed, and an iron salt and a phosphorus source are added to carry out a precipitation reaction in water to obtain an ferric phosphate material; The iron phosphate material, the lithium source and the carbon source are mixed and then calcined to obtain the lithium iron phosphate material.

6. The preparation method according to claim 5, characterized in that: The preparation method of the large-size iron phosphate crystal seeds partially coated with polydopamine comprises: mixing and dispersing the large-size iron phosphate crystal seeds and a surfactant in a Tris-HCl buffer solution containing dopamine hydrochloride, stirring for reaction, filtering, washing and drying to obtain the large-size iron phosphate crystal seeds partially coated with polydopamine.

7. The preparation method according to claim 6, characterized in that: The method for preparing the large-size iron phosphate seeds partially coated with polydopamine comprises at least one of the following features 1 to 6: Feature 1: The surfactant is an anionic surfactant, and the concentration of the surfactant in the Tris-HCl buffer solution is 0.1-3 g / L; Feature 2: The mass ratio of the large-size iron phosphate seed crystals to the surfactant is 50:1-5; Feature 3: The particle size of the large-particle iron phosphate seed crystals is 400-1500nm; Feature 4: The pH of the Tris-HCl buffer solution is 8-8.5; Feature 5: The concentration of the dopamine hydrochloride in the Tris-HCl buffer solution is 0.1-0.3 mg / mL; Feature 6: The stirring rate of the stirring reaction is 500-1000 rpm, and the time is 20-30 hours.

8. The preparation method according to claim 5, characterized in that: The preparation method includes at least one of the following features A to G: Feature A: The vacuum dehydration temperature is 160-190 ° C, the time is 1-1.5h; Feature B: The particle size of the small-particle iron phosphate seed crystals is 200-600 nm; Feature C: The volume ratio of the modified iron phosphate seed crystals to the small particle size iron phosphate seed crystals is 0.9-1.5:1; Feature D: The volume ratio of the total volume of the modified ferric phosphate seed crystals and the small-particle ferric phosphate seed crystals to the water is 1:4-12; Feature E: The concentration of the iron salt in the water is 0.5-1.2 mol / L; Feature F: The molar ratio of the iron element of the iron salt to the phosphorus element of the phosphorus source is 1:1-1.5; Feature G: The stirring rate of the precipitation reaction is 350-750 rpm.

9. A positive electrode sheet, characterized in that: The positive electrode plate comprises the lithium iron phosphate material according to any one of claims 1 to 4, or the lithium iron phosphate material obtained by the preparation method according to any one of claims 5 to 8.

10. A secondary battery, characterized in that: Including the positive electrode sheet as described in claim 9.

Citation Information

Patent Citations

  • Film-coated and / or granulated calcium-containing compounds and use thereof in pharmaceutical compositions

    CN101355927A

  • Negative electrode material, and electrochemical device and electronic device including same

    CN111146414A

  • High-compaction high-performance lithium iron phosphate positive electrode material and preparation method thereof

    CN114497479A

  • Lithium iron phosphate-based precursor, positive electrode material and preparation method and application of lithium iron phosphate-based precursor and positive electrode material

    CN117682494A

  • Modified lithium iron phosphate material and preparation method thereof, positive pole piece and secondary battery

    CN117800305A

Cited By

  • Battery cell, battery device and electric device

    CN119994000A

  • Battery cell, battery device, and electric device

    CN119994000B

  • Positive pole piece and secondary battery

    CN121306984A

  • A positive electrode sheet, a secondary battery

    CN121306984B

  • Lithium iron phosphate material and application thereof

    CN122771349A